Membrane remodelling triggers maturation of excitation-contraction coupling in 3D-shaped human-induced pluripotent stem cell-derived cardiomyocytes - Kermani, Fatemeh; Mosqueira, Matias; Peters, Kyra; Lemma, Enrico D.; Rapti, Kleopatra; Grimm, Dirk; Bastmeyer, Martin; Laugsch, Magdalena; Hecker, Markus; Ullrich, Nina D. (Basic research in cardiology, 2023)
The prospective use of human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) for cardiac regenerative medicine strongly depends on the electro-mechanical properties of these cells, especially regarding the Ca2+-dependent excitation-contraction (EC) coupling mechanism. Currently, the immature structural and functional features of hiPSC-CM limit the progression towards clinical applications. Here, we show that a specific microarchitecture is essential for functional maturation of hiPSC-CM. Structural remodelling towards a cuboid cell shape and induction of BIN1, a facilitator of membrane invaginations, lead to transverse (t)-tubule-like structures. This transformation brings two Ca2+ channels critical for EC coupling in close proximity, the L-type Ca2+ channel at the sarcolemma and the ryanodine receptor at the sarcoplasmic reticulum. Consequently, the Ca2+-dependent functional interaction of these channels becomes more efficient, leading to improved spatio-temporal synchronisation of Ca2+ transients and higher EC coupling gain. Thus, functional maturation of hiPSC-cardiomyocytes by optimised cell microarchitecture needs to be considered for future cardiac regenerative approaches.